Copyright Infringement and Legal Effects on Providers and Users of Illegal Streaming Services in the Perspective of Criminal Law - Ulandari, Mega; Guntara, Deny; Abas, Muhamad; Pratama, Raka Indra (LEGAL BRIEF, 2025)
The rapid development of digital technology presents new challenges in enforcing copyright law, especially against illegal streaming sites that distribute copyrighted content without permission. This study examines the legal implications for providers and users of such platforms under Law No. 28 of 2014 on Copyright. It analyzes the regulatory framework and criminal sanctions applicable to both actors using a normative juridical method with statutory and case study approaches. Findings indicate that providers may be directly sanctioned for violating creators’ economic rights under Article 113(2)–(3), while users are only liable if actively involved in unlawful dissemination. Enforcement faces structural and technical barriers, including the complaint-based nature of the offense, digital evidence complexity, and cross-border jurisdiction. Academically, this research enriches digital copyright discourse and offers relevant legal interpretations. Practically, it recommends strengthening cyber law enforcement and updating legal norms to respond effectively to copyright violations in the digital era